Penentuan Resistivity Tanah Di Dalam Menetapkan Area Pemasangan Grounding Gardu Distribusi 20 Kv Mengunakan Kombinasi Grid dan Rod di Kampus Politeknik Negeri Padang - Junaidi Asrul -; Wiwik Wiharti -; Efendi - -; Firmansyah - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
To obtain a small earth (near zero) resistivity value is determined by the number of planted electrodes and soil type properties. Difficulty in obtaining this small resistivity value often errors in estimating soil properties or soil type resistance so that failure to obtain soil barriers often occurs.To determine the desired amount of material can be measured soil type resistor value, by measuring the soil resistivity value so that the estimated material cost estimation can be achieved well. then in this research using geoelectric method with Schlumberger configuration. Schlumberger method is a method with a constant system of spacing rules with the note of the 'n' multiplier is the comparison of the distance between the C1-P1 or (C2-P2) electrodes with P1-P2. The instrument used is a resistivity meter ( Naniura) equipped with four electrodes which have the ability to read output voltage response due to current injected into the ground surface through two current electrodes and two potential electrodes. In this study used progress to map the 2D isoresistivity beneath the measured surface. .The results of this soil resistivity measurement can be determined with certainty the amount of material used and the cost of workmanship provided to establish the proper grounding system to be attached to a 20 kV Distribution substation at the State Polytechnic Padang State Electricity Laboratory. So that the grounding system in pairs meet the standards that have been determined and can be categorized both and safe for humans and equipment for grounding Distribution Distributors 20 kV Electricity Engineering Laboratory at the State Polytechnic Campus Padang